The Implementation of the Cooperative Learning Model Using Puzzle Media to Enhance the Reading Skills of Second-Grade Elementary School Students - Asnita Hasibuan; Ica Sintia Sitorus; Suwinandi Lumbantoruan; Tambun Santoso Saragih (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Low beginning reading proficiency among second-grade students at SD Negeri 068007 Medan Tuntungan was associated with limited reading interest, low classroom participation, difficulties in recognizing letters and blending syllables, and insufficiently varied instructional methods. This study aimed to examine the implementation of a cooperative learning model assisted by puzzle media in improving students’ beginning reading skills during the 2025/2026 academic year. Classroom action research was conducted in two cycles, each comprising planning, action, observation, and reflection. The participants were second-grade students at SD Negeri 068007 Medan Tuntungan. Data were collected through observations, reading tests, interviews, and documentation and analyzed using qualitative and quantitative descriptive techniques. The findings indicate that the cooperative learning model assisted by puzzle media increased students’ participation and improved their ability to recognize letters, blend syllables, and read simple words and sentences. Learning outcomes also improved, as demonstrated by an increase in the number of students achieving the Minimum Mastery Criterion. The study concludes that integrating cooperative learning with puzzle media effectively supports the development of beginning reading skills by creating a more active, collaborative, and engaging learning environment. These findings provide practical implications for primary school teachers seeking interactive instructional strategies to address early literacy difficulties and strengthen students’ participation and reading achievement.